EFFECT OF GINGER, LEMURU FISH OIL SAPONIFICATION AND OLIVE OIL ON COMPOSITION FATTY ACID OF BEEF - Siwitri Kadarsih (Jurnal Agroindustri, 2014)
The objective was to get beef that contain unsaturated fatty acids (especially omega 3 and 6), so as to improve intelligence, physical health for those who consume. The study design using CRD with 3 treatments, each treatment used 4 Bali cattle aged approximately 1.5 years. Observations were made 8 weeks. Pasta mixed with ginger provided konsentrat. P1 (control); P2 (6% saponification lemuru fish oil, olive oil 1%; rice bran: 37.30%; corn: 62.70%; KLK: 7%, ginger paste: 100 g); P3 (lemuru fish oil saponification 8%, 2% olive oil; rice bran; 37.30; corn: 62.70%; KLK: 7%, ginger paste: 200 g). Konsentrat given in the morning as much as 1% of the weight of the cattle based on dry matter, while the grass given a minimum of 10% of the weight of livestock observation variables include: fatty acid composition of meat. Data the analyzies qualitative. The results of the study showed that the composition of saturated fatty acids in meat decreased and an increase in unsaturated fatty acids, namely linoleic acid (omega 6) and linolenic acid (omega 3), and deikosapenta deikosaheksa acid.Keywords :